Application of Faraday Effect as an Authentication Technique for Vegetable Oils - Abu-Taha, M. I.; Halasa, M. A.; Abu-Samreh, M. M. (New Trends in Physical Science Research Vol. 4, 2022)
The Verdet constant for olive and other vegetable oils has been measured in this work. Different types of vegetable oils also have different Verdet constants, this allows olive oil authentication from adulteration by other cheap vegetable oils. Most of the current work on edible oil adulteration is based on chromatographic analysis. This work attempts to employ Faraday effect as a sampling technique. The study of samples maintained for various lengths of time under various storage conditions revealed that each olive oil sample has a Verdet constant value that is dependent on the following factors: production year, sample history (i.e. storage conditions), and geographical area. Oils stored in room light exhibited lower levels of tocopherol, carotenoid, and chlorophyll than oils stored in the dark. Oils and fats constitute one of the three major classes of food products, the others being proteins and carbohydrates. Preliminary findings suggested that the Faraday Effect could be used to detect olive oil adulteration, implying that the effect could be proposed as a food authentication technique if calibration curves and standard Verdet constants values could be prepared for comparison with those of the samples under investigation. A further study is needed to determine the relation between the value of the Verdet constant and the primary and secondary oxidation products, oil component contents etc.